ANALISIS KADAR SERUM FERITIN DI KARSINOMA PAYUDARA (Analysis of Ferritin Levels in Carcinoma Mammae) - Sriwati Atjo; Uleng Bahrun; Hardjoeno Hardjoeno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Carcinoma Mammae is a malignant disease originating from mammary parenchyma, and the second largest cause of death inthe world. Ferritin is a marker of neoplasia, which levels are increased in non-metastatic carcinoma mammae and more increased inmetastatic carcinoma mammae. This cross sectional study was conducted during June 2012 in carcinoma mammae patients of theWahidin Sudirohusodo Hospital, Ibnu Sina Hospital and Labuang Baji Hospital in Makassar. The aim of this study was to know theserum ferritin levels in metastatic and non-metastatic carcinoma mammae. In this study, 56 samples were obtained and grouped intometastatic and non-metastatic carcinoma mammae patients based on the Tumor, Node, Metastasis (TNM). Ferritin test was conductedby ECLIA method using Elecsys Analyzer Kit 2010 (Roche, USA). The study showed that the average ferritin concentration in advancedstage of carcinoma mammae (155.45 ng/mL) was higher than in the early stage (82.74 ng/m). The Mann Whitney test showed significantdifferences between the early and advanced stage (p=0.01), the median ferritin value in metastatic carcinoma mammae was higherthan non-metastatic (79.85 ng/mL). The Mann Whitney test showed significant differences between metastatic and non - metastaticcarcinoma mammae patients (p=0.00). Based on this study, it can be concluded, that ferritin levels can be used as a biomarker to predictthe progressivity of carcinoma mammae.